Transcriptome Analysis Reveals miR-302a-3p Affects Granulosa Cell Proliferation by Targeting DRD1 in Chickens - Liu, Yufang; Zhou, Zuyang; Zhang, Hui; Han, Haiyin; Yang, Junqi; Li, Wenting; Wang, Kejun (Frontiers in Genetics, 2022)
Egg production is an important economic trait in layer chickens, as higher yields bring higher profits. Small yellow follicles (SYLs) development is a key determinant of chicken reproductive performance; however, most SYLs are not selected and undergo atresia in the process of chicken reproduction. Hence, we aimed to use the high-throughput technology to analyze the differences between the SYLs mRNA transcriptome of high- (H) and low-yield (L) Taihang layer hens, and reveals the potential regulator of the candidate gene involved in controlling the egg production rate. Here, we constructed six cDNA libraries between H and L Taihang hens then performed by high-throughput sequencing. Comparison between the H and L groups showed 415 differentially expressed genes (DEGs), of which 226 were up-regulated and 189 were down-regulated in the high-yield group. Differentially enriched biological functions and processes were identified using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) database analysis. Ten of the candidate genes that may play a crucial role in the development of small yellow follicles from hens according to the results of previously studies. Homology analysis indicated that DRD1 was highly conservative in various species, and which may be a potential target for improving egg production. We also identified a miRNA miR-302a-3p that functions in follicle cell proliferation by targeting DRD1. The RT-qPCR results showed that the expression of DRD1 and miR-302a-3p showed the opposite trend in the SYLs of high- and low- yielding chickens. Luciferase assays showed that miR-302a-3p targets the 3’UTR of DRD1. Overexpression of miR-302a-3p significantly inhibited the expression of DRD1 in chicken granulose cells (GCs) (P<0.01). Moreover, the functional experiments revealed that by targeting DRD1, miR-302a-3p plays an inhibitor of GCs proliferation. The DEGs from RNA-seq analysis might be related to the egg production of Taihang laying hens. Moreover, enrichment analysis suggested that DRD1 is involved in egg production. Bioinformatics analysis and functional assays suggest that miR-302a-3p affects chicken GCs proliferation by targeting DRD1. Our data expand the knowledge base of genes whose functions are important for egg production, and the molecular mechanisms of egg high-yield regulation in chicken small yellow follicles.